Comparison of the 2022 ACR/EULAR classification criteria with the 1990 ACR classification criteria for Takayasu arteritis - Tecer, Duygu; Kaya, Mehmet Nur; Kılıç, Özlem; Yılmaz, Sedat (Sarcoidosis, Vasculitis and Diffuse Lung Diseases, 2025)
Background and aim: Takayasu arteritis (TAK) mostly affects the aorta and its major branches and has an unclear origin. This study aimed to compare the 1990 American College of Rheumatology (ACR) classification criteria with the 2022 ACR/European League Against Rheumatism (EULAR) classification criteria for TAK on the basis of clinical data analysis of patients with TAK and other major vascular diseases.Methods: This retrospective study was conducted in a single-center. The results included 34 TAK patients routinely followed at a tertiary rheumatology center from October 2017 to February 2024. The accuracy, sensitivity, specificity, positive predictive values (PPV), negative predictive values (NPV), and area under the receiver operating characteristic (ROC) curve (AUC) of the classification criteria were compared.Results: The sensitivity (91.2%), specificity (90.9%), PPV (93.9%), NPV (86.9%), accuracy (94.4%) and AUC (0.983 (0.957-0.998)) of the 2022 ACR/EULAR classification criteria for TAK were higher than those of the 1990 ACR classification criteria for TAK (76.4%, 86.3%, 88.9%, 64.2% and 0.75, respectively), and the difference in AUC was statistically significant (0.860 (0.757-0.963), p < 0.001).Conclusions: This study found that the 2022 ACR/EULAR classification criteria were more suitable for our patient population and had better classification performance than those in 1990, which can be supported in clinical practice. Our study needs to be supported by future multicenter prospective studies with larger patient numbers.